(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the problems encountered by a person deprived of liberty in terms of health and medical services, peace and order, food and hydration, and facilities and detention cells. The results of the study reveal that the problems encountered by a person deprived of liberty were evaluated as “Disagree” in terms of health and medical services, peace and order, food and hydration, and facilities and detention cells, and there is a measure may propose to address the Problem Encountered by Person Deprived of Liberty. This study necessarily recommended improvement and providing additional detention facilities for the person deprived of liberty supporting government officials, national agencies, and other authorities. For additional medical personnel, it is important to understand the structural conditions within PDL facilities. Additional medical facilities increasing jail congestion have more challenges in access to health services in one of their medical facilities. Additional classroom (for bible teaching and therapy sessions) is necessarily recommended to build an additional classroom for treatment. This program’s very important for the person deprived of liberty to help improve the attitude and spirit to have the will to change himself and then give him support to improve.